Meningkatkan Kemandirian Belajar Dalam Pembelajaran Pak Dengan Model Problem Based Learning Materi Kemampuanku Terbatas Fase D Kelas VII SMP Negeri 1 Dolok Panribuan - Helena Carni Nopita Parhusip; Anselmus Joko Prayitno; Roida Sihombing3 (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Education is currently still believed to be a very effective medium in building independent learning. The learning independence that the author means in this research is related to a condition where students are able to process themselves in making decisions and are responsible for the actions they take. To achieve the educational goals proclaimed by the government, the author as a Catholic Religious Education teacher wants to take part in This includes increasing the learning independence of students in PAK which is still very minimal, especially for students in the Simalungun Regency environment and especially class VII students at SMP Negeri 1 Dolok Panribuan. This type of research is a type of classroom action research carried out in class with two face-to-face action cycles. To obtain data, the techniques used are observation, tests and documentation. Hypothesis analysis and testing techniques are quantitative descriptive, namely comparing the level of learning independence before this research was carried out, namely the initial condition of students' learning independence, increasing student independence after action I (cycle I) and increasing student independence after action II (cycle II), then reflected. Based on the research results, it can be concluded that there has been an increase in the independence of phase D class VII students in each indicator by implementing the Problem Based Learning learning model.